Effect of Functional Bread Rich in Potassium, γ-Aminobutyric Acid and Angiotensin-Converting Enzyme Inhibitors on Blood Pressure, Glucose Metabolism and Endothelial Function: A Double-blind Randomized Crossover Clinical Trial. Issue 46 (November 2015) - Becerra-Tomás, Nerea; Guasch-Ferré, Marta; Quilez, Joan; Merino, Jordi; Ferré, Raimon; Díaz-López, Andrés; Bulló, Mònica; Hernández-Alonso, Pablo; Palau-Galindo, Antoni; Salas-Salvadó, Jordi
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Because it has been suggested that food rich in γ-aminobutyric acid (GABA) or angiotensin-converting enzyme inhibitor (ACEI) peptides have beneficial effects on blood pressure (BP) and other cardiovascular risk factors, we tested the effects of low-sodium bread, but rich in potassium, GABA, and ACEI peptides on 24-hour BP, glucose metabolism, and endothelial function. A randomized, double-blind, crossover trial was conducted in 30 patients with pre or mild-to-moderate hypertension, comparing three 4-week nutritional interventions separated by 2-week washout periods. Patients were randomly assigned to consume 120 g/day of 1 of the 3 types of bread for each nutritional intervention: conventional wheat bread (CB), low-sodium wheat bread enriched in potassium (LSB), and low-sodium wheat bread rich in potassium, GABA, and ACEI peptides (LSB + G). For each period, 24-hour BP measurements, in vivo endothelial function, and biochemical samples were obtained. After LSB + G consumption, 24-hour ambulatory BP underwent a nonsignificant greater reduction than after the consumption of CB and LSB (0.26 mm Hg in systolic BP and −0.63 mm Hg in diastolic BP for CB; −0.71 mm Hg in systolic BP and −1.08 mm Hg in diastolic BP for LSB; and −0.75 mm Hg in systolic BP and −2.12 mm Hg in diastolic BP for LSB + G, respectively). Diastolic BP at rest decreased significantly during the LSB + G intervention, although there were no significant differences in changes between interventions. There were no significant differences between interventions in terms of changes in in vivo endothelial function, glucose metabolism, and peripheral inflammatory parameters. Compared with the consumption of CB or LSB, no greater beneficial effects on 24-hour BP, endothelial function, or glucose metabolism were demonstrated after the consumption of LSB + G in a population with pre or mild-to-moderate hypertension. Further studies are warranted to clarify the effect of GABA on BP, preferably using a specific design for noninferiority trials and ambulatory BP monitoring as a measure of BP. This study was registered at Current Controlled Trials as ISRCTN31436822